A cerium oxide interface modified Fe-CaO bifunctional material, a preparation method and application thereof

CN122895002APending Publication Date: 2026-10-13NINGXIA MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611293883.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0003]但传统Fe-CaO复合材料在高温循环过程中存在晶粒易长大、骨架坍塌、烧结严重等导致循环稳定性急剧下降;同时工业烟气普遍存在O2与水蒸气,易造成活性位点覆盖、结构腐蚀、催化性能快速衰减,难以满足长期服役要求

Benefits of technology

[0016]本发明中,制备方法具有优异抗烧结性能,CeO2纳米界面层实现晶界物理阻隔,高温循环下晶粒尺寸稳定,无明显烧结坍塌,结构强度高。烟气适应性强,可耐受烟气中O2、水蒸气侵蚀,活性衰减速率显著降低,解决复杂工况下快速失活难题,材料双重功能稳定,同步保持CaO高效CO2吸附性能与Fe基催化还原性能,CO选择性高,吸附-催化协同效率高,制备得到的CeO2界面修饰Fe-CaO双功能材料具有良好的工艺优势,原料廉价易得、制备流程简洁、设备通用性强、条件可控,适合批量生产,可直接应用于电厂、工业窑炉烟气净化与碳捕集系统。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122895002A_ABST
    Figure CN122895002A_ABST
Patent Text Reader

Abstract

The application discloses a cerium oxide interface modified Fe-CaO bifunctional material, which comprises the following components in mass fraction: 60-85 parts of CaO; 5-15 parts of Fe; and 5-15 parts of CeO2, and discloses a preparation method and application thereof. The application is suitable for the field of environmental functional composite materials, and the preparation method has excellent sintering resistance. A CeO2 nano interface layer realizes physical blocking of a grain boundary, and the grain size is stable under high-temperature circulation, without obvious sintering collapse, and the structural strength is high. The flue gas adaptability is strong, and the material can resist O2 and water vapor erosion in the flue gas, and the activity decay rate is significantly reduced, so that the problem of rapid deactivation under complex working conditions is solved, the material has stable double functions, the high-efficiency CO2 adsorption performance of CaO and the Fe-based catalytic reduction performance are simultaneously maintained, the CO selectivity is high, the adsorption-catalysis synergistic efficiency is high, and the prepared CeO2 interface modified Fe-CaO bifunctional material has good process advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental functional composite materials, and in particular to a cerium oxide interface-modified Fe-CaO bifunctional material, its preparation method, and its application. Background Technology

[0002] Fe-CaO bifunctional materials combine the CO2 adsorption and capture properties of CaO with the catalytic and redox properties of Fe, and have the potential for large-scale application in flue gas treatment and carbon capture.

[0003] However, traditional Fe-CaO composite materials suffer from rapid grain growth, framework collapse, and severe sintering during high-temperature cycling, leading to a sharp decline in cycling stability. Simultaneously, the presence of O2 and water vapor in industrial flue gas can cause active site coverage, structural corrosion, and rapid degradation of catalytic performance, making it difficult to meet long-term service requirements. Conventional doping and loading modifications can only alleviate sintering or poisoning problems individually, failing to simultaneously achieve high-temperature anti-sintering and flue gas oxygen and water resistance stability, thus limiting their industrial application.

[0004] To address the aforementioned technical bottlenecks, there is an urgent need to design a CeO2 interface modification scheme. Through grain boundary barrier, oxygen storage buffer, and interface structure regulation, this scheme can achieve highly stable dual-function operation of Fe-CaO materials under complex flue gas conditions, thus overcoming the shortcomings of existing technologies. Summary of the Invention

[0005] In view of the above problems, the present invention is proposed to provide solutions that overcome or at least partially solve the above problems.

[0006] According to one aspect of the present invention, a cerium oxide interface-modified Fe-CaO bifunctional material, its preparation method, and its application are provided, comprising the following components by mass fraction: 60–85 parts CaO; 5-15 parts Fe; 5 to 15 parts CeO2.

[0007] Preferably, in the cerium oxide interface-modified Fe-CaO bifunctional material, CaO is the main component, Fe is a low-proportion catalytic phase, and CeO2 is the interface modifier.

[0008] Preferably, in the cerium oxide interface-modified Fe-CaO bifunctional material, CeO2 is uniformly distributed in 5-20 nm nanoparticles at the Fe-CaO grain interface, surface and interior, forming a continuous or semi-continuous interface barrier layer to suppress high-temperature sintering and improve oxygen and water vapor resistance.

[0009] Secondly, a method for preparing a cerium oxide interface-modified Fe-CaO bifunctional material includes the following steps: (1) Preparation of precursor solution: Dissolve calcium nitrate in water to prepare a 1.5-3.0 mol / L solution; prepare ferric nitrate to prepare a 0.05-0.25 mol / L solution and heat and stir at 90℃ for 1 h; prepare cerium nitrate solution according to the final CeO2 mass content of 5%-15%.

[0010] (2) Preparation of bifunctional materials: calcium nitrate, iron nitrate and cerium nitrate solutions were mixed to obtain a precursor mixture. Citric acid was added as a chelating agent and structure regulator. The mixture was magnetically stirred at 80°C for 3-4 h to obtain a composite gel, which was then dried at 90-120°C overnight. (3) Segmented calcination: The dried product is pre-calcined in a muffle furnace at 300-450℃ for 2-3 hours, and then calcined in segments at 600℃ and 850℃ in sequence, with each segment held for 1-2 hours. After natural cooling, the Fe-CaO bifunctional material with cerium oxide interface modification is obtained.

[0011] Preferably, in step (1), the ferric nitrate solution must be dispersed under heating conditions of 80-100°C.

[0012] Preferably, the amount of citric acid added in step (2) is 6.5 to 8.5 g.

[0013] Preferably, the segmented calcination in step (3) is used to avoid rapid agglomeration of crystals and maintain the CeO2 nano-dispersion and interfacial barrier structure.

[0014] Thirdly, the application of a cerium oxide interface-modified Fe-CaO bifunctional material, wherein the cerium oxide interface-modified Fe-CaO bifunctional material is a bifunctional adsorption catalyst that combines CO2 adsorption performance and CO2 catalytic conversion performance, and is suitable for carbon capture and purification of complex industrial flue gas containing oxygen and water vapor.

[0015] Fourthly, an application of a cerium oxide interface-modified Fe-CaO bifunctional material for CO2 adsorption, capture, and catalytic conversion of oxygen- and water-containing high-temperature flue gas from power plants and industrial kilns.

[0016] In this invention, the preparation method exhibits excellent anti-sintering properties. The CeO2 nano-interface layer provides physical barrier at grain boundaries, ensuring stable grain size under high-temperature cycling with no significant sintering collapse and high structural strength. It demonstrates strong flue gas adaptability, tolerating O2 and water vapor erosion in the flue gas, and significantly reducing the activity decay rate, thus solving the problem of rapid deactivation under complex operating conditions. The material exhibits stable dual functions, simultaneously maintaining the high-efficiency CO2 adsorption performance of CaO and the catalytic reduction performance of Fe-based materials. It exhibits high CO selectivity and high adsorption-catalytic synergistic efficiency. The prepared CeO2 interface-modified Fe-CaO bifunctional material possesses significant process advantages: inexpensive and readily available raw materials, a simple preparation process, versatile equipment, and controllable conditions, making it suitable for mass production. It can be directly applied to flue gas purification and carbon capture systems in power plants and industrial kilns.

[0017] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, and in order to make the above and other objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described below. Attached Figure Description

[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a schematic diagram of CeO2 distribution provided in an embodiment of the present invention; Figure 2 A schematic diagram of a dual-functional material provided in an embodiment of the present invention; Figure 3 This is a schematic diagram of the CO2 capture and conversion process provided in an embodiment of the present invention; Figure 4 This is a schematic diagram of the XRD pattern of the reduced sample provided in an embodiment of the present invention; Figure 5 A schematic diagram of O2-TPD analysis provided in an embodiment of the present invention. Figure 1 ; Figure 6 A schematic diagram of O2-TPD analysis provided in an embodiment of the present invention. Figure 2 ; Figure 7 The figure shows the experimental results of no O2 and no water vapor provided in the embodiments of the present invention; Figure 8 The experimental results of O2 and water vapor are provided for embodiments of the present invention. Detailed Implementation

[0020] Exemplary embodiments of the present disclosure will now be described in more detail with reference to the accompanying drawings. While exemplary embodiments of the present disclosure are shown in the drawings, it should be understood that the present disclosure may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the disclosure to those skilled in the art.

[0021] The terms "comprising" and "having," and any variations thereof, in the specification, embodiments, claims, and drawings of this invention are intended to cover non-exclusive inclusion, such as including a series of steps or units.

[0022] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0023] Example 1 8.43 g of calcium nitrate tetrahydrate and 6.5 g of citric acid were dissolved in 50 mL of deionized water along with quantitative amounts of ferric nitrate nonahydrate and cerium nitrate, respectively, controlling the Fe content to be 5-15% of the CaO mass and the CeO2 content to be 5-15 wt%. The solution was placed in a 90℃ constant temperature water bath for 3-4 h to obtain a composite sol. This sol was then dried in a 120℃ oven for 10-12 h to obtain a dry sol. The dry sol was pre-calcined in a muffle furnace at 450℃ for 2 h, and then calcined at 650℃ and 850℃ for 2 h each to obtain the target bifunctional material. The obtained target material is shown in the attached figure. Figure 2 .

[0024] Example 2 (without CeO2 control) The sample obtained from Example 1, x in sample xFe-CaO-yCeO2, represents an iron content of 10% of the calcium oxide mass and y represents a CeO2 content of 0%. 0.5g of the sample was placed in a quartz glass reactor. After pre-reduction with 15% H2 at 650°C for 1.5h, the sample was purged with nitrogen for 10min. The CO2 / N2 mixture was then switched to capture, followed by nitrogen purification for 10min. A hydrogenation reaction was then initiated by introducing 15% H2. The CO2 capture and conversion process is detailed in Appendix [Appendix]. Figure 3 At a CO2 concentration of 10%, an H2 concentration of 15%, a temperature of 650 °C, a flow rate of 100 mL / min, and a normal pressure, the catalyst exhibited an initial CO2 adsorption capacity of 18.57 mmol / g, a CO yield of 8.7 mmol / g, a CO2 conversion rate of 62%, and a CO selectivity of 100%.

[0025] Example 3 (CeO 25%) The sample obtained from Example 1, xFe-CaO-yCeO2, where x represents 10% iron content (calcium oxide mass) and y represents 5% CeO2 content, was 0.5g loaded into a quartz glass reactor. After pre-reduction with 15% H2 at 650℃ for 1.5h, the sample was purged with nitrogen for 10min. A 10% CO2 / N2 collection method was then used, followed by nitrogen purification for 10min, and then hydrogenation was carried out by introducing 15% H2. At a CO2 concentration of 10%, an H2 concentration of 15%, 650℃, 100 mL / min, and atmospheric pressure, the initial CO2 adsorption capacity of the catalyst was 15.5 mmol / g, the CO yield was 7.8 mmol / g, the CO2 conversion rate was 70%, and the CO selectivity was 100%.

[0026] Example 4 (CeO2 12%, optimal ratio) The sample obtained from Example 1, where x in sample xFe-CaO-yCeO2 represents an iron content of 10% by mass of calcium oxide and y represents a CeO2 content of 12%, was 0.5 g loaded into a quartz glass reactor. After pre-reduction with 15% H2 at 650°C for 1.5 h, the sample was purged with nitrogen for 10 min. The XRD pattern of the reduced sample is shown in the attached figure. Figure 4 The catalyst was switched to a 10% CO2 / N2 capture method, followed by nitrogen purification for 10 min, and then 15% H2 was introduced for hydrogenation. At a CO2 concentration of 10%, an H2 concentration of 15%, a temperature of 650 °C, a flow rate of 100 mL / min, and atmospheric pressure, the initial CO2 adsorption capacity of the catalyst was 16.68 mmol / g, the CO yield was 10.52 mmol / g, the CO2 conversion rate was 72%, and the CO selectivity was 100%.

[0027] Example 5 (flue gas containing O2+H2O, CeO2 5%) Repeat Example 3, with an iron content of 10% of CaO mass and a CeO2 content of 5%. 0.5 g of the sample was placed in a quartz glass reactor. After pre-reduction with 15% H2 at 650°C for 1.5 h, the sample was purged with nitrogen for 10 min. The mixture was then switched to a 10% CO2 / N2 collection system, followed by nitrogen purification for 10 min, and then hydrogenation was carried out using 15% H2. At a CO2 concentration of 10%, an H2 concentration of 15%, a 5% O2 + H2O / N2 ratio, a temperature of 650°C, a flow rate of 100 mL / min, and atmospheric pressure, the initial CO2 adsorption capacity of the catalyst was 11 mmol / g, the CO yield was 6.5 mmol / g, the CO2 conversion rate was 62%, and the CO selectivity was 100%.

[0028] Example 6 (flue gas containing O2+H2O, CeO2 12%) Example 4 was repeated with an iron content of 10% of CaO mass and a CeO2 content of 12%. 0.5 g of the sample was placed in a quartz glass reactor. After pre-reduction with 15% H2 at 650 °C for 1.5 h, the sample was purged with nitrogen for 10 min. The mixture was then switched to a 10% CO2 / N2 collection system, followed by nitrogen purification for 10 min, and then hydrogenation was carried out using 15% H2. At a CO2 concentration of 10%, an H2 concentration of 15%, a 5% O2 + H2O / N2 concentration, 650 °C, 100 mL / min, and atmospheric pressure, the initial CO2 adsorption capacity of the catalyst was 15.95 mmol / g, the CO yield was 8.36 mmol / g, the CO2 conversion rate was 68.9%, and the CO selectivity was 100%. After 10 cycles, the CO2 adsorption capacity was 11.50 mmol / g, the CO yield was 5.73 mmol / g, and the stability was significantly better than the sample with a low CeO2 ratio.

[0029] Example 7 To investigate the oxygen transport characteristics at the CeO2 interface, O2-TPD analysis was performed on Examples 5 and 6. (See reference appendix...) Figure 5 The results showed that the oxygen desorption curve changed significantly with increasing CeO2 content. When the CeO2 content was 12%, the oxygen desorption curve changed more rapidly. III The zone desorption exhibits the highest lattice oxygen content, implying stronger lattice oxygen migration in Example 6, which is conducive to the formation of interfacial oxygen vacancies. (Refer to Appendix) Figure 6 The results showed that higher CeO2 content increased the intensity of oxygen vacancies, promoting CO2 activation. In-situ infrared spectroscopy was used to investigate and verify the intermediate reaction process of CO2 capture and conversion by O2 and water vapor in simulated flue gas. Results from experiments without O2 and water vapor are shown in the appendix. Figure 7 Reference notes on O2 and water vapor Figure 8 The results showed that O2 and water vapor have an impact on CO2 capture and conversion. During the reaction, water vapor and O2 affect the reduction ability of the active phase, which can easily lead to catalyst aggregation and deactivation.

[0030] Example 8 A cerium oxide interface-modified Fe-CaO bifunctional material is disclosed, consisting of an Fe-CaO active matrix and a CeO2 modifier. CeO2 acts as an anti-sintering barrier, a flue gas tolerance modifier, and an interface regulator. By mass, CaO comprises 60%, Fe active components 25%, and CeO2 15%. CeO2 particles (5 nm) are uniformly distributed at the Fe-CaO grain interfaces, surfaces, and pores, forming a continuous or semi-continuous physical barrier layer to inhibit high-temperature grain agglomeration. Simultaneously, CeO2's oxygen storage capacity creates abundant oxygen vacancies, mitigating the erosion of the active phase by O2 and water vapor, thus improving the material's structural stability and bifunctionality retention under complex flue gas conditions.

[0031] Furthermore, the precursor uses a water-soluble composite system of calcium nitrate, iron nitrate, and cerium nitrate, with citric acid as a chelating agent and structure directing agent to regulate the sol-gel process and grain growth rate, ensuring uniform dispersion of components.

[0032] Furthermore, based on the adsorbent mass, the content of additives in the bifunctional material is 5%.

[0033] Furthermore, based on the mixed precursor solution, the content of chelating agent and structure directing agent in the bifunctional material is 6.5g.

[0034] Example 9 A cerium oxide interface-modified Fe-CaO bifunctional material is disclosed, consisting of an Fe-CaO active matrix and a CeO2 modifier. CeO2 acts as an anti-sintering barrier, a flue gas tolerance modifier, and an interface regulator. By mass, CaO comprises 70%, Fe active components 20%, and CeO2 10%. CeO2, in 10nm nanoparticle form, is uniformly distributed at the Fe-CaO grain interface, surface, and pores, forming a continuous or semi-continuous physical barrier layer that inhibits high-temperature grain agglomeration. Simultaneously, CeO2's oxygen storage capacity creates abundant oxygen vacancies, mitigating the erosion of the active phase by O2 and water vapor, thus improving the material's structural stability and bifunctionality retention under complex flue gas conditions.

[0035] Furthermore, the precursor uses a water-soluble composite system of calcium nitrate, iron nitrate, and cerium nitrate, with citric acid as a chelating agent and structure directing agent to regulate the sol-gel process and grain growth rate, ensuring uniform dispersion of components.

[0036] Furthermore, based on the adsorbent mass, the content of additives in the bifunctional material is 10%.

[0037] Furthermore, based on the mixed precursor solution, the content of chelating agent and structure directing agent in the bifunctional material is 7g.

[0038] Example 10 A cerium oxide interface-modified Fe-CaO bifunctional material is disclosed, consisting of an Fe-CaO active matrix and a CeO2 modifier. CeO2 acts as an anti-sintering barrier, a flue gas tolerance modifier, and an interface regulator. By mass, CaO comprises 85%, Fe active components 5%, and CeO2 10%. CeO2, in 20nm nanoparticle form, is uniformly distributed at the Fe-CaO grain interface, surface, and pores, forming a continuous or semi-continuous physical barrier layer that inhibits high-temperature grain agglomeration. Simultaneously, CeO2's oxygen storage capacity creates abundant oxygen vacancies, mitigating the erosion of the active phase by O2 and water vapor, thus improving the material's structural stability and bifunctionality retention under complex flue gas conditions.

[0039] Furthermore, the precursor uses a water-soluble composite system of calcium nitrate, iron nitrate, and cerium nitrate, with citric acid as a chelating agent and structure directing agent to regulate the sol-gel process and grain growth rate, ensuring uniform dispersion of components.

[0040] Furthermore, based on the adsorbent mass, the content of additives in the bifunctional material is 15%.

[0041] Furthermore, based on the mixed precursor solution, the content of chelating agent and structure directing agent in the bifunctional material is 8.5g.

[0042] Example 11: A method for preparing a cerium oxide interface-modified Fe-CaO bifunctional material, comprising the following steps: (1) Calcium nitrate was dissolved in deionized water to prepare a 1.5 mol / L solution; ferric nitrate was prepared into a 0.05 mol / L solution according to the calcium-based mass ratio, and heated and stirred at 90°C for 1 h; cerium nitrate solution was prepared quantitatively according to a final CeO2 content of 5 wt%, and each component was dispersed separately and evenly. Calcium nitrate, ferric nitrate, and cerium nitrate solutions were mixed to obtain a precursor mixture, and 6.5 g of citric acid was added as a chelating agent and structure regulator. The mixture was magnetically stirred at 80°C for 1 h to form a transparent composite sol; the sol was placed in a 90°C oven and dried overnight to obtain a dry gel. The dry gel was transferred to a muffle furnace and pre-calcined at 300°C for 2 h to remove organic matter and moisture; then the temperature was raised to 600°C and 850°C in stages, and each stage was held for 1 h. The mixture was then naturally cooled to room temperature to obtain a cerium oxide interface-modified Fe-CaO bifunctional material.

[0043] (2) Preparation of xFe-CaO-CeO2: Ferric nitrate nonahydrate solutions with different x contents were stirred for 1 hour and then placed in a constant temperature water bath at 90℃ for 3 hours to form a composite sol. The composite sol was then dried in an oven at 120℃ for 10 hours. It was then pre-calcined in a muffle furnace at 300℃ for 1 hour and calcined in two stages at 600℃, with each stage held for 1 hour, to obtain the bifunctional material. (3) Preparation of Fe-CaO-yCeO2: Cerium nitrate with different y contents was mixed with a precursor solution and stirred for 1 h, then placed in a constant temperature water bath at 90℃ for 3 h to form a composite sol. Then, the composite sol was dried in an oven at 120℃ for 10 h. Then, it was pre-calcined in a muffle furnace at 300℃ for 1 h, and then calcined in two stages at 600℃, with each stage holding for 1 h, to obtain a bifunctional material; Furthermore, the iron-calcium bifunctional adsorption catalyst prepared in step (3) with cerium oxide interface modification has CeO2 particles of 5 nm uniformly dispersed in Fe-CaO, as shown in the attached figure. Figure 1 .

[0044] Example 12: A method for preparing a cerium oxide interface-modified Fe-CaO bifunctional material, comprising the following steps: (1) Calcium nitrate was dissolved in deionized water to prepare a 2 mol / L solution; ferric nitrate was prepared into a 0.1 mol / L solution according to the calcium-based mass ratio, and heated and stirred at 90°C for 1 h; cerium nitrate solution was prepared quantitatively according to a final CeO2 content of 10 wt%, and each component was dispersed separately and evenly. Calcium nitrate, ferric nitrate, and cerium nitrate solutions were mixed to obtain a precursor mixture, and 7 g of citric acid was added as a chelating agent and structure regulator. The mixture was magnetically stirred at 80°C for 2 h to form a transparent composite sol; the sol was placed in a 100°C oven and dried overnight to obtain a dry gel. The dry gel was transferred to a muffle furnace and pre-calcined at 400°C for 2 h to remove organic matter and moisture; then the temperature was raised to 600°C and 850°C in stages, and each stage was held for 1.5 h. The mixture was then naturally cooled to room temperature to obtain a cerium oxide interface-modified Fe-CaO bifunctional material.

[0045] (2) Preparation of xFe-CaO-CeO2: Ferric nitrate nonahydrate solutions with different x contents were stirred for 1.5 h and then placed in a constant temperature water bath at 90℃ for 3.5 h to form a composite sol. The composite sol was then dried in an oven at 120℃ for 11 h. It was then pre-calcined in a muffle furnace at 400℃ for 1.5 h, and calcined in two stages at 600℃ and 850℃, with each stage holding for 1.5 h, to obtain the bifunctional material. (3) Preparation of Fe-CaO-yCeO2: Cerium nitrate with different y contents was mixed with a precursor solution and stirred for 1.5 h, then placed in a constant temperature water bath at 90℃ for 3.5 h to form a composite sol. Then, the composite sol was dried in an oven at 120℃ for 11 h. Then, it was pre-calcined in a muffle furnace at 400℃ for 1.5 h, and then calcined in two stages at 600℃ and 850℃, with each stage holding time of 1.5 h, to obtain a bifunctional material; Furthermore, the iron-calcium bifunctional adsorption catalyst prepared in step (3) with cerium oxide interface modification has CeO2 particles of 15 nm uniformly dispersed in Fe-CaO, as shown in the attached figure. Figure 1 .

[0046] Example 13: A method for preparing a cerium oxide interface-modified Fe-CaO bifunctional material, comprising the following steps: (1) Calcium nitrate was dissolved in deionized water to prepare a 3.0 mol / L solution; ferric nitrate was prepared into a 0.25 mol / L solution according to the calcium-based mass ratio, and heated and stirred at 90°C for 1 h; cerium nitrate solution was prepared quantitatively according to a final CeO2 content of 15 wt%, and each component was dispersed separately and evenly. Calcium nitrate, ferric nitrate, and cerium nitrate solutions were mixed to obtain a precursor mixture, and 8.5 g of citric acid was added as a chelating agent and structure regulator. The mixture was magnetically stirred at 80°C for 3 h to form a transparent composite sol; the sol was placed in an oven at 120°C and dried overnight to obtain a dry gel. The dry gel was transferred to a muffle furnace and pre-calcined at 450°C for 2 h to remove organic matter and moisture; then the temperature was raised to 600°C and 850°C in stages, and each stage was held for 2 h. The mixture was then naturally cooled to room temperature to obtain a cerium oxide interface-modified Fe-CaO bifunctional material.

[0047] (2) Preparation of xFe-CaO-CeO2: Ferric nitrate nonahydrate with different contents of x and mixed precursor solutions were stirred for 2 h, and then placed in a constant temperature water bath at 90℃ for 4 h to form a composite sol. Then, the composite sol was dried in an oven at 120℃ for 12 h. Then, it was pre-calcined in a muffle furnace at 450℃ for 2 h, and then calcined in two stages at 600℃ and 850℃, with each stage holding time of 2 h, to obtain the bifunctional material; (3) Preparation of Fe-CaO-yCeO2: Cerium nitrate of different contents was mixed with a precursor solution and stirred for 2 hours, then placed in a constant temperature water bath at 90℃ for 4 hours to form a composite sol. The composite sol was then dried in an oven at 120℃ for 12 hours. Then it was pre-calcined in a muffle furnace at 450℃ for 2 hours, and then calcined in two stages at 600℃ and 850℃, with each stage holding for 2 hours, to obtain a bifunctional material; Furthermore, the iron-calcium bifunctional adsorption catalyst prepared in step (3) with cerium oxide interface modification has CeO2 particles of 25 nm uniformly dispersed in Fe-CaO, as shown in the attached figure. Figure 1 .

[0048] By adopting the above technical solution: (1) The preparation method of this invention has excellent anti-sintering properties. The CeO2 nano-interface layer achieves physical barrier of grain boundaries. The grain size is stable under high temperature cycling, with no obvious sintering collapse and high structural strength. It has strong flue gas adaptability and can withstand the erosion of O2 and water vapor in flue gas. The activity decay rate is significantly reduced, solving the problem of rapid deactivation under complex working conditions.

[0049] (2) The material prepared by the method of the present invention has dual functions and stability, and simultaneously maintains the high efficiency of CaO CO2 adsorption performance and Fe-based catalytic reduction performance, with CO selectivity of 100% and high adsorption-catalysis synergistic efficiency.

[0050] (3) The CeO2 interface modified Fe-CaO bifunctional material prepared according to the method of the present invention has good process advantages. The raw materials are cheap and readily available, the preparation process is simple, the equipment is versatile, and the conditions are controllable. It is suitable for mass production and can be directly applied to power plant and industrial kiln flue gas purification and carbon capture systems.

[0051] The above specific embodiments further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above are merely specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A cerium oxide interface-modified Fe-CaO bifunctional material, characterized in that, By mass fraction, it includes the following components: 60–85 parts CaO; 5-15 parts Fe; 5 to 15 parts CeO2.

2. The cerium oxide interface-modified Fe-CaO bifunctional material as described in claim 1, characterized in that, In the aforementioned cerium oxide interface-modified Fe-CaO bifunctional material, CaO is the main component, Fe is a low-proportion catalytic phase, and CeO2 is the interface modifier.

3. The cerium oxide interface-modified Fe-CaO bifunctional material as described in claim 1, characterized in that: In the cerium oxide interface-modified Fe-CaO bifunctional material, CeO2 is uniformly distributed in 5-20 nm nanoparticles at the Fe-CaO grain interface, surface and interior, forming a continuous or semi-continuous interface barrier layer, which is used to suppress high-temperature sintering and improve oxygen and water vapor resistance.

4. The method for preparing a cerium oxide interface-modified Fe-CaO bifunctional material as described in any one of claims 1-3, characterized in that, Includes the following steps: (1) Preparation of precursor solution: Dissolve calcium nitrate in water to prepare a 1.5-3.0 mol / L solution; prepare ferric nitrate to prepare a 0.05-0.25 mol / L solution and heat and stir at 90℃ for 1 h; prepare cerium nitrate solution according to the final CeO2 mass content of 5%-15%; (2) Preparation of bifunctional materials: calcium nitrate, iron nitrate and cerium nitrate solutions were mixed to obtain a precursor mixture. Citric acid was added as a chelating agent and structure regulator. The mixture was magnetically stirred at 80°C for 3-4 h to obtain a composite gel, which was then dried at 90-120°C overnight. (3) Segmented calcination: The dried product is pre-calcined in a muffle furnace at 300-450℃ for 2-3 hours, and then calcined in segments at 600℃ and 850℃ in sequence, with each segment held for 1-2 hours. After natural cooling, the Fe-CaO bifunctional material with cerium oxide interface modification is obtained.

5. The method for preparing a cerium oxide interface-modified Fe-CaO bifunctional material as described in claim 4, characterized in that, In step (1), the ferric nitrate solution must be dispersed under heating conditions of 80-100℃.

6. The method for preparing a cerium oxide interface-modified Fe-CaO bifunctional material as described in claim 4, characterized in that, In step (2), the amount of citric acid added is 6.5–8.5 g.

7. The method for preparing a cerium oxide interface-modified Fe-CaO bifunctional material as described in claim 4, characterized in that, In step (3), segmented calcination is used to avoid rapid agglomeration of crystals and maintain the CeO2 nano-dispersion and interfacial barrier structure.

8. The application of the cerium oxide interface-modified Fe-CaO bifunctional material as described in any one of claims 1-3, characterized in that: The cerium oxide interface-modified Fe-CaO bifunctional material is a bifunctional adsorption catalyst that combines CO2 adsorption and CO2 catalytic conversion performance, and is suitable for carbon capture and purification of complex industrial flue gas containing oxygen and water vapor.

9. The application of the cerium oxide interface-modified Fe-CaO bifunctional material as described in any one of claims 1-3, characterized in that: It is used for CO2 adsorption, capture and catalytic conversion of high-temperature flue gas containing oxygen and water vapor in power plants and industrial kilns.